Transforming Accounting Education Through Educators’ Consciousness: A Theatrical Perspective - Ari Kamayanti (Journal of Accounting Research, Organization and Economics, 2018)
AbstractObjective – Study aims to portrait how changes in accounting education should start with ac-counting educators’ consciousness and how to trigger this consciousness. Design/methodology – This study offers alternative perspective to enhance accounting education through educators’ consciousness. This study took place in ACURA that was established in May 1986 in Surabaya by a group of public state university lecturers. By employing a qualitative approach namely dramaturgical interventionism study in a private university, the changes of accounting lecturers consciousness were observed and presented. Results – It is found that educators’ consciousness is necessary to change the course of accounting education to be geared for civilization. The most important trait that an accounting education has is a continuously critically conscious (3C) character.  However, the critical consciousness is only part that will make up ‘self’ consciousness. Research limitations/implications – This findings could be transferrable to other institutions with similar context.  This also opens up another door to further research, especially one that is applicative in nature.